Analisis Tingkat Laju Erosi pada Area Cover Crop Jarang dan Lebat Dalam Pemulihan Lahan Bekas Tambang pada Lahan Revegetasi I18 PT Bharinto Ekatama - Ahmad Sobirin (Prosiding ESEC, 2023)
Changes in land cover that were originally limited production forest areas were converted into mining areas causing environmental degradation. The I18 revegetation land was originally a forest area with a denudational hilly landform covered with various tropical forest vegetation of Kalimantan converted into a coal mining area. and to be returned to forest areas through land rehabilitation. The purpose of this study was to analyze the rate of erosion in sparse and dense cover crop areas in the restoration of reclamation land on I18 revegetation land. This research uses survey methods and field mapping in data collection and processing. Vegetation density data was collected at 20 sample points by purposive sampling using the quadrat transect method. Determination of the erosion rate using the stick method with details of 12 sticks in the rare cover crop area and 6 sticks in the dense cover crop area with volume weight testing using laboratory methods referring to SNI 03-3637-1994 and descriptive analysis. The results showed that the erosion rate value of the cover crop area was rarely 161.13 tons / ha while the dense cover crop area had an erosion value of 1.57 tons / ha. Cover crop areas rarely have a higher erosion rate than dense cover crop areas, more susceptible to soil damage with an area reaching 55.46% of the I18 area has the potential for erosion so that it needs improvement through conservation.